The 1st International Electronic Conference on Biomolecules: Natural and Bio-Inspired Therapeutics for Human Diseases 2020
DOI: 10.3390/iecbm2020-08733
|View full text |Cite
|
Sign up to set email alerts
|

Lentinan for Integrative Cancer Treatment: An Umbrella Review

Abstract: The aim of this review is to understand whether lentinan can be a useful integrative remedy for cancer patients. PubMed, EMBASE, Web of Science, Cochrane Library, and Google Scholar were screened for relevant meta-analyses from inception to September 29th, 2020. After database search, 8 meta-analyses met inclusion criteria. Retrieved evidence reported that lentinan may be useful to improve response rate, 1-year survival, performance status, quality of life, and radio/chemotherapy toxicity when administered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, consumers and public health authorities are increasingly concerned about the use of antibiotics to balance animal health and the development of antimicrobial resistance on farms (Ruegg, 2017;Nobrega et al, 2020). Lentinan is a kind of polysaccharide extracted from Lentinus edodes, which has no toxicity and possesses various pharmacological activities such as anticancer, antibacterial, and antiviral effects (Antonelli et al, 2020;Lv et al, 2020;Zi et al, 2020). Thus, the anti-inflammatory function of lentinan on LPS-stimulated mastitis was carried out, and the mechanism involved was explored.…”
Section: Discussionmentioning
confidence: 99%
“…However, consumers and public health authorities are increasingly concerned about the use of antibiotics to balance animal health and the development of antimicrobial resistance on farms (Ruegg, 2017;Nobrega et al, 2020). Lentinan is a kind of polysaccharide extracted from Lentinus edodes, which has no toxicity and possesses various pharmacological activities such as anticancer, antibacterial, and antiviral effects (Antonelli et al, 2020;Lv et al, 2020;Zi et al, 2020). Thus, the anti-inflammatory function of lentinan on LPS-stimulated mastitis was carried out, and the mechanism involved was explored.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory experiments indicate that many edible and medicinal mushrooms, such as the Ascomycetes and the Basidiomycetes, have antioxidant properties [11,12]. Recent studies have also reported that supplementation of extracts derived from medicinal mushrooms can help boost immune defenses [13], exert a potential antiproliferative effect [14,15], reduce insulin resistance and lipid levels [16,17], show an anticaries action [18], improve mood in patients suffering from major depressive disorder [19], diminish disease-related fatigue [20], and ameliorate cognitive functions in subjects affected by pre-dementia [21]. Some of these therapeutic effects are likely owed to fungal beta-glucans, well known for their immune-modulating and prebiotic effects [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Lentinan has been considered an adjunctive therapy to radio/chemotherapy for patients diagnosed with solid tumors, improving response rate, one-year survival, performance status, quality of life and radio/chemotherapy toxicity [ 168 ]. A clinical trial evaluated the intravenous administration of lentinan extract in combination with two chemotherapeutic compounds (5-FU and Tegafur) in patients with advanced or recurrent stomach, colorectal and breast cancers.…”
Section: Applications Of β-Glucansmentioning
confidence: 99%